Design And Development Of Auto Depth Control Of Remotely Operated Vehicle Using Thrusters System - Ali, Fara Ashikin; Mohd Aras, Mohd Shahrieel; Ab Azis, Fadilah; Sulaima, Mohamad Fani; Jaafar, Ismail (2014)
Remotely Operated Vehicles are underwater robots designed specifically for surveillance, monitoring and collecting data for underwater activities. In the underwater vehicle industries, the thruster is an important part in controlling the direction, depth and speed of the ROV. However, there are some ROVs that cannot be maintained at the specified depth for a long time because of disturbance. This paper proposes an auto depth control using a thruster system. A prototype of a thruster with an auto depth control is developed and attached to the previously fabricated UTeM ROV. This paper presents the operation of auto depth control as well as thrusters for submerging and emerging purposes and maintaining the specified depth. The thruster system utilizes a microcontroller as its brain, a piezoresistive strain gauge pressure sensor and a DC brushless motor to run the propeller. Performance analysis of the auto depth control system is conducted to identify the sensitivity of the pressure sensor, and the accuracy and stability of the system. The results show that the thruster system performs well in maintaining a specified depth as well as stabilizing itself when a disturbanceoccurs even with a simple proportional controller used to control the thruster, where the thruster is an important component of the ROV.